Addressing the prolonged ension gap - Dohun Kim (Korea Development Institute (KDI), 2023)
As the age for National Pension eligibility rises, creating an income gap, many older people typically offset this by increasing their labor earnings, studies suggest. Those facing a pension gap tend to increase earnings without an accompanying rise in poverty or reduction in consumption. However, households with excessive medical expenses struggle to fully offset the reduced pension, as increased labor income doesn't completely make up for the pension shortfall. Given the ongoing upward trajectory of the pensionable age, meticulous monitoring of elderly employment trends and bolstering support for prolonged employment are of paramount importance. For immediate relief, older households, constricted by caregiving obligations and facing labor supply limitations, require further reinforcement through targeted support programs.
Keywords: 330